2021
DOI: 10.1007/s00267-021-01432-7
|View full text |Cite
|
Sign up to set email alerts
|

Governance Challenges at the Interface of Food Security and Biodiversity Conservation: A Multi-Level Case Study from Ethiopia

Abstract: Ensuring food security while also protecting biodiversity requires a governance system that can address intra- and intersectoral complexity. In this paper, we sought to explore the governance challenges surrounding food security and biodiversity conservation through an empirical study in Jimma zone, southwestern Ethiopia. We used bottom-up snowball sampling to identify stakeholders and then held semi-structured interviews with 177 stakeholders across multiple levels of governance. We also conducted 24 focus gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 69 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Southwestern Ethiopia is characterized by rich but declining biodiversity (Friis et al, 2011; Oostdijk, 2021). People's livelihood strongly relies on the ecosystem services generated from the landscape (Jiren et al, 2022; Jiren, Leventon, et al, 2021). Over the last decades, due to pressure from a myriad of local and regional factors (Tadesse et al, 2014), the landscape has been undergoing rapid social–ecological change (Fischer et al, 2021; Jiren, Bergsten, et al, 2018; Jiren, Hanspach, et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Southwestern Ethiopia is characterized by rich but declining biodiversity (Friis et al, 2011; Oostdijk, 2021). People's livelihood strongly relies on the ecosystem services generated from the landscape (Jiren et al, 2022; Jiren, Leventon, et al, 2021). Over the last decades, due to pressure from a myriad of local and regional factors (Tadesse et al, 2014), the landscape has been undergoing rapid social–ecological change (Fischer et al, 2021; Jiren, Bergsten, et al, 2018; Jiren, Hanspach, et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, within our study area, the absence of a clear land use plan is one of the key inhibitors of the harmonious integration of multiple uses of the landscape (Jiren, Leventon, et al, 2021). Notably, however, although southwestern Ethiopia is the focus of this study, the types of challenges identified, and the methodological approach taken here are likely relevant to many other rapidly changing social–ecological systems.…”
Section: Introductionmentioning
confidence: 99%
“…The interviews focused on identifying collaborative links between stakeholders, and on governance challenges affecting food security and biodiversity. Social network analysis was applied to investigate and visualize patterns of stakeholder collaboration (Jiren et al 2018a;Bergsten et al 2019), while qualitative data on governance process challenges were analysed through content analysis (Jiren et al 2021).…”
Section: Methods Used In the Sub-projectsmentioning
confidence: 99%
“…between biodiversity conservation and agricultural development). These process-related challenges not only affected food security and biodiversity conservation in isolation, but also made their integration more challenging (Jiren et al 2021).…”
Section: Summary Of Key Findings In the Sub-projectsmentioning
confidence: 99%
“…of decision-making) can pose challenges and opportunities for biodiversity conservation 105 . For ecologists, it is important to be aware of this complexity – for example, top-down decision-making could easily overlook the needs of less influential community members (such as poor households or women); there can be large discrepancies between ideas generated at high levels of government versus local capacities to implement such ideas; and staff might fluctuate frequently creating a lack of institutional continuity and history 105 . This complexity requires ecologists to engage differently with decision-makers than simply through the publication of scientific outputs.…”
Section: Lesson 5: Use a Social-ecological Systems Perspective For Co...mentioning
confidence: 99%